한·중 제조기업의 중간재경쟁력 및 핵심역량이 고객가치와 기업성과에 미치는 영향에 관한 실증적 연구 - 노형진(Hyung-Jin Rho) (韓國컴퓨터情報學會論文誌, 2014)
The purpose of this paper is to study the effects of the competitiveness of intermediate goods and enterprise's core competency on customer value and enterprise performance. And it is surely meaningful to investigate the intermediate product competitiveness with the variable of interest to recent corporate values and corporate customers with business performance by exploring their relationships. This research focuses on the intermediate goods competitive dimension and the company's core competency, and then several models are proposed. The research model is based on the existing core competencies of the conceptual model, which consists of intermediate goods competitive, core competencies, product innovation, product reliability, customer value and corporate performance. The automobile company in China and Korea are focused in this paper; empirical analysis method is applied to examine the relationships in these areas. The concept of core competencies in the existing competitive enterprises in product and process is defined as the relative advantage. Eight hypotheses are introduced for statistical hypothesis testing. Employees and typical intermediate products in automotive companies in China and Korea are investigated. 본 연구는 기업의 중간재경쟁력 및 기업의 핵심역량과 내부고객가치 및 기업성과의 관계를 밝혀내고자 하는 데 목적이 있다. 연구모형의 검정에서는 양국 조직구성원들이 느끼는 고객가치와 기업성과에 대한 관계를 파악하고자 한다. 연구의 결과를 요약하면 다음과 같다. 한국 기업집단의 경우는, 중간재경쟁력은 제품의 신뢰성과 제품의 혁신성에 유의한 영향을 미치고, 핵심역량은 제품의 신뢰성과 제품의 혁신성에 유의한 영향을 미치는 것으로 나타났다. 제품의 신뢰성은 고객가치에 유의한 영향을 미치고, 고객가치는 기업의 성과에 유의한 영향이 있다. 그러나 제품의 혁신성은 고객가치에 유의하지 않은 영향이 나타났다. 한편 중국 기업집단에서 중간재경쟁력은 제품의 신뢰성, 제품의 혁신성에 유의한 영향을 나타냈다. 또한 핵심역량은 제품의 혁신성에 유의한 영향을 나타냈지만 제품의 신뢰성에 유의하지 않은 영향이 나타났다. 그리고 제품의 신뢰성은 고객가치에 유의하지 않은 영향이 있지만, 제품의 혁신성은 고객가치에 유의한 영향을 나타냈다. 마지막으로 고객가치는 기업성과에 유의한 영향을 미치는 것으로 나타났다.